(untitled) (Orfeu, 2022)
In this article we approach the relationship between the colonization process in the North Santa Catarina State and the concomitant development of the Paróquia Santa Cruz de Canoinhas, between the end of the 19th century and the beginning of the 20th, aiming a description of the presence of sacred music in that scenario. Using records from the curch, cartorials, iconography and bibliography of the areas covered, we present a mapping of the process of development of the musical structure at the Paróquia, having as temporal landmarks the beginning of the Jesuit missions in the region (1891) and the year of change of the first vicar (1923). The discussion is based on aspects of the Romanized Church of Pius IX and the determinations of the Motu Proprio “Inter pastoralis officci sollicitudines” of Pius X. It is understood that for the Saxon community of the region, the church and its apparatus (including music) were important for the life of the colonizers, composing the social network in their stays in the young villages of the state. We also aim to draw attention to the need to expand the musicological investigations about less privileged fields, such as the contryside of Santa Catarina.